2016
DOI: 10.1186/s13065-016-0147-2
|View full text |Cite
|
Sign up to set email alerts
|

Disposable screen printed sensor for the electrochemical detection of methamphetamine in undiluted saliva

Abstract: BackgroundMethamphetamine has an adverse effect on the ability to drive safely. Police need to quickly screen potentially impaired drivers therefore a rapid disposable test for methamphetamine is highly desirable. This is the first proof-of-concept report of a disposable electrochemical test for methamphetamine in undiluted saliva.ResultsA screen printed carbon electrode is used for the N,N′-(1,4-phenylene)-dibenzenesulfonamide mediated detection of methamphetamine in saliva buffer and saliva. The oxidized med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 18 publications
2
14
0
1
Order By: Relevance
“…Those technologies enable to measure proteins, DNA, transcripts (mRNA), electrolytes, and small molecules in saliva. 162 Currently developed tools include electrochemical sensing, 189 on-chip qRT-PCR, 190 fiber optic microsphere-based arrays, 191 high-throughput DNA microarrays, 192 surface plasmon resonance-based fiber optic sensors, 193 and microchip-based electrophoretic immunoassay. 137 The new avenue of point-of-care diagnostics for ''lab-ona-chip'' provides a new facet of point-of-care diagnostics, because it concurrently enables the detection of multiple biomarkers, and thus simultaneous diagnosis of many diseases.…”
Section: Technologies For Salivary Diagnosticsmentioning
confidence: 99%
“…Those technologies enable to measure proteins, DNA, transcripts (mRNA), electrolytes, and small molecules in saliva. 162 Currently developed tools include electrochemical sensing, 189 on-chip qRT-PCR, 190 fiber optic microsphere-based arrays, 191 high-throughput DNA microarrays, 192 surface plasmon resonance-based fiber optic sensors, 193 and microchip-based electrophoretic immunoassay. 137 The new avenue of point-of-care diagnostics for ''lab-ona-chip'' provides a new facet of point-of-care diagnostics, because it concurrently enables the detection of multiple biomarkers, and thus simultaneous diagnosis of many diseases.…”
Section: Technologies For Salivary Diagnosticsmentioning
confidence: 99%
“…2016 marked the first use of a disposable electrode for the detection of MA, within undiluted saliva samples, through utilisation of N,N′-(1,4-phenylene)-dibenzenesulfoamide as a mediator. 25 Although this work was promising for the detection of MA via portable electrochemical methodologies within biological matrices, the detection limits achieved lay outwith the clinically relevant range. Detection limits for MA have been improved via utilisation of ECL sensors, through employment of the traditional luminophore, [Ru(bpy) 3 ] 2+ , facilitating mediated oxidation of the amine moiety within the species.…”
Section: Introductionmentioning
confidence: 93%
“…Furthered though the proven ability of ECL sensors to offer direct drug detection within range of complex matrices, including biological fluids, without the requirement of any separation or purification strategies. [16][17][18][19][20][21][22][23][24][25][26][27] The detection of MA within biological fluids adopts a twopronged approach, whereby identification of MA abuse is paired with detection of AMP as one of its primary metabolites. 8,[28][29][30] Following ingestion, MA is readily absorbed into the blood stream, with excretion primarily though the renal system following hepatic metabolism, resulting in the primary metabolites; AMP following the N-demethylation process and para-hydroxymethamphetamine ( p-OHMA) following para-hydroxylation.…”
Section: Introductionmentioning
confidence: 99%
“…Screen-printed sensors were also used to detect methamphetamine. The researchers used a screen-printed carbon electrode and a mediator (N,N′-(1,4-phenylene)-dibenzenesulfonamide) that once oxidized will react with methamphetamine (MAMP) and form an adduct that can be subjected to electrochemical reduction [ 42 ]. Using a double square wave voltammetry technique, they were able to detect concentrations of MAMP as low as 400 ng/mL in 55 s. They concluded that although the response time of the sensor was very good, the detection limit was higher than what currently used methods can ensure and further work is needed for the improvement of the method.…”
Section: Illicit Drug Detection Using Screen-printed Electrodesmentioning
confidence: 99%